1998
DOI: 10.1111/j.1399-6576.1998.tb05305.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative autotransfusion is associated with modest reduction of allogeneic transfusion in prosthetic hip surgery

Abstract: Autotransfusion has a limited efficacy to decrease the need for allogeneic blood, and other blood-saving methods should be added for this purpose. It is difficult to predict the need for allogeneic blood preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 23 publications
3
53
1
1
Order By: Relevance
“…One was the drain loss which was the sum of the drain collection on Day 1 (Day 1 drain loss) and on Day 2 (Day 2 drain loss). The other parameter was the total blood loss calculated by the hemoglobin balance method [12,19], which involved measuring hemoglobin levels at several stages. This calculation gave a better estimation of the combined external loss, ie, intraoperative loss plus drain loss and the internal (hidden) blood loss.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One was the drain loss which was the sum of the drain collection on Day 1 (Day 1 drain loss) and on Day 2 (Day 2 drain loss). The other parameter was the total blood loss calculated by the hemoglobin balance method [12,19], which involved measuring hemoglobin levels at several stages. This calculation gave a better estimation of the combined external loss, ie, intraoperative loss plus drain loss and the internal (hidden) blood loss.…”
Section: Methodsmentioning
confidence: 99%
“…From these, the total blood loss in milliliters was calculated as follows [12,19]: total blood loss = 1000 * Hb loss /Hb i .…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not clear whether use of Cell Saver decreases the need for other transfusions in this patient population. While some studies have found that Cell Saver use decreases the need for other blood transfusion in orthopedic surgery [1][2][3][4], others have found its use to be of little or no benefit [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examining the usefulness of Cell Saver in orthopedic surgery have included mostly adult patients [1][2][3][4][5], with the exception of Siller et al [6], who studied adolescents undergoing spinal fusion for idiopathic scoliosis. To our knowledge, there has been no published study examining scoliosis patients of all ages and etiologies to determine the usefulness of Cell Saver in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…After completion of each cycle, the bowl can be filled again as often as required. The hematocrit of the final erythrocyte supension is regulated by an optical sensor in the centrifugation chamber, targeting a packed cell volume of 55-70% 4,5,[11][12][13] . Modified cell separation can also be performed by passing collected blood repeatedly through a vortex mixing filter with longitudinal channels and microporous plastic membranes (Haemocell System 350 ® , Haemonetics TM ), under continuous washing with saline solution 8 .…”
Section: Figurementioning
confidence: 99%